KARAKTERISTIK OBJECT LINKING AND EMBEDDING PADA PROGRAM APLIKASI PENGELOLAAN DATA SPASIAL - IIham Marsudi (Inersia : Jurnal Teknik Sipil dan Arsitektur, 2006)
AbstractThis research aims to clarify the characteristic of Object Linkedand Embedding (OLE), copy-paste, and copy-paste special facilities inthe software applied for spatial data processing especially in Excel,AutoCAD, Maplnfo, and arcView.Microsoft Word (document) is chosen as a client in this research:while Excel, AutoCAD, Maplnfo, and arcView as the servers. Updatingprocess on each server is conducted to have cognize of any datachanges implemented on the client.The result shows that there is not any data change on updatingprocess applied on Excel, AutoCAD, and MaplnfointoMicrosoft Word(document): but conversely updating process of arcView on the clienthas changed the data.Key words: embedded, linked, Copy Paste, Copy Paste Special.